Studies on genetic variability of Capsicum frutescens var. Cakra Hijau induced by ethyl methane sulphonate (EMS) using SSR marker - Rahmattullah, Nur; Khrisnamurty, Ramya; Senthil, Kalaiselvi; Arumingtyas, Estri Laras (Current Botany, 2020)
Genetic variability of wild type and EMS induced mutant cayenne peppers (Capsicum frutescens) var. Cakra Hijau is studied morphological traits and simple sequence repeat (SSR) markers. Phenotypic characters were investigated using standard pepper descriptors. The polymorphic SSR marker Ca19, Ca26, Ca52, Ca56, and Ca96were analyzed using unweighted pair group methods with arithmetic means (UPGMA) with Jaccard’s similarity index. The Polymorphic information content (PIC) value ranging from 0-0.228 with the highest index on Ca96. The Morphological traits showed of clusters (6 clades) with a lower cut-off value (0.2568) than SSR-based dendrogram did (4 clades; 0,5108). Therefore, genetic variability induced by EMS mutant were differentiated using morphological and SSR genotyping.